Düzce'deki Kuzey Kafkas (Çerkes) evleri - Aksan, Ferda (Fen Bilimleri Enstitüsü, 1997)
MÖ 5000 yılında tarih sahnesine çıkan Kuzey Kafkaslar- varlıklarını uzun yıllar boyunca Kuzey Kafkas Dağları'nda birarada yaşayarak devam ettirmişlerdir. Yaşadıkları yerlerin doğal özelliklerine uygun olan etnik malzemelerle- geleneksel sayılabilecek konutlar yapmışlardır. Daha sonra savaşlar ve baskılar sonucunda 19.yy'ın ikinci yarısında (1864 yılında)- büyük bir grup olarak (nüfusun yansından çoğu) Osmanlı topraklarına göç etmişler ve çok farklı bölgelere dağılmışlardır. İlk zamanlar yerleri sürekli değiştirildiği için çok basit srüktürlü konutlar inşa etmişler- kesin yerleştikleri bölgelerde de tekrar yer değiştirebileceklerini düşünerek inşa ettikleri basit evlere- ihtiyaçlarına ve alışkanlıklarına uygun eklemeler yapmışlardır. Gerek yerleştikleri coğrafi ve iklimsel özelliklere- gerekse ellerindeki malzemeye uygun olarak yaptıkları evler ile Kuzey Kafkasya'daki evler geleneksel anlamda- form ve fonksiyon olarak birbirine benzese de- birtakım farklılıkları da vardır. "Batı Karadeniz Bölgesi'ndeki Kuzey Kafkas Evleri"- adlı bu çalışma dört ana bölümden oluşmuştur. Birinci bölümde- tezin amacı- eldeki kaynaklar ve bunların kullanım yöntemleri ile araştırmanın yapıldığı coğrafi sınırlar ele alınmıştır. İkinci bölümde- Kuzey Kafkasya ve burada yaşayan insanlara ait etnik ve kültürel hayat anlatılmış- sosyal hayatın oluşumuna etken olabilecek mitoloji- din- dil gibi faktörlere ve diğer kültürlerle olan ilişkilere değinilmiş ve sonuç olarak ortaya çıkan- geleneksel konutlara ilişkin bilgiler verilmiştir. Üçüncü bölümde Kuzey Kafkaslar'ın Osmanlı topraklarına göçü ve daha sonraki yıllarda Düzce İlçesi'ne yerleşimleri incelenmiş- bölgenin coğrafi özellikleri ve iklimi göz önüne alınarak- halen mevcut olan ilk yerleşim örnekleri- rölöve ve fotoğraflarla birlikte tanıtılmıştır. Dördüncü bölümde- geleneksel Kafkas evleri ve Kuzey Kafkaslar'ın Türkiye'de inşa ettikleri evler ile ilgili karşılaştırmalar yapılmış ve farklılıklar üzerinde durulmuştur.

We met the people so called Circassians throughout history first at 3000's BC They have longtime been lived in Northern Caucasian Mountains as compact social groups. They have created a certain vernacular architecture, suitable of the natural materials and climatic conditions. The wars and social oppressions created an immigration consisting more than half of the population, beginning by 1864 on the different parts of The Ottoman territories. On the recently settled areas, the have first constructed simple structures having temporary qualities then permanent. They have sometimes made additions to the new dwellings respecting the needs and customs. The new dwellings, shaped by the geographical, climatic or available material on the newly settled areas got similarities dealing the form and the function with Northern Caucasian ones, but the differentiation are also at hand. The thesis, so called "Northern Caucasian Houses in Düzce" has been divided to the four parts. The aim, the sources has been dealt in the first part, as well as the method and geographical limits. What we know about the dwellings of the Northern Caucasian people. Who has immigrated to the actual Turkish territories beginning by 1864 and continued. Through the following years are given Circassians settlements and houses built on the Caucasian territories on the motherland are studied. The data which has been obtained is compared briefly with the ones obtained from the dwellings built on Turkish territories. The sources dealing with Northern Caucasian settlements give mostly written data. There is a lack of information on the old houses and settlements except some photographs and books which are on Northern Caucasian people and territories at the and of the expeditions. The houses have been disappeared following the immigrations, the wars and natural disasters like the earthquakes and the new dwellings are designed as single type, suitable for the building politic of the USSR The written sources are formed by the travelers, as the journey notes on the Northern Caucasian territories, like a certain account of photographs. The studies in Turkey are the surveys and measurements on the Circasia houses from the villages at Düzce. XVll Circasia people are pushed to settle down on Ottoman territories and the new habitations consist different areas. The new habitations were not permanent, as the inhabitants had had to move frequently. Actually thirty cities comprises Circassian people in Turkey. The study is limited with a certain geographical area, in order to get a strict data, as inhabited geographical layout in Turkey has not a compact shape. The thesis is dealt with the settlements and dwellings from Circassian villages at Düzce-Bolu, Western Black Sea area. Ethnological and cultural layout on the Northern Caucasian is the subject of the second part. The social aspects like the language, the mythology, the religion which has shaped social life are dealt, as well as the cultural transferred with other populations, so the traditional formations of the dwellings could be clear enough. The land so called Caucasia has Azak Denizi and The Black Sea at the west, Hazar Denizi at the east, Iran and Turkey at the south. It has formed the southern borders of the old USSR, before the political changes in Europe. The topographical shaping of the Caucasia has large flat meadows at the north, Riyan and Kura regions are low at the south. The valleys which are narrow and high enough in some areas has been profitable for the people, to be protected. The traditions are very important to fix the rules defining space formation and organization. Traditional and custom are the main aspect to shape the social life in Northern Caucasia. The structural of the space and generally houses between Northern Caucasian people, as part of the social life, has been affected both tribal transference and feudal ideology, which forms certain social standards. This effects are the source of the social organization formed by the proksemik. The symbolic meanings of the living spaces like the house, the garden or common places are not different between. Northern Caucasian people as the parameters do not differ cultural. In villages, through the social and administrative systems, the property rights consist of the common and personal owner ships. The houses are built close to the properties and all are surrounded by some hedges. The agriculture, the stock breeding and hard crafts are shaping the economy. The millets, barley and the corn have produced on the agricultural layout as well as boza and wine have been consumed. Opium poppy and opium have been produced in South-eastern Caucasia. The house types on Northern Caucasian Mountains are the one with a flat roof. Underground construction and tower houses until the middle of 19.th century. Both types are born in the beginning of the historical ages. Some differentiation had been at hand throughout history but the characteristic in general were permanent. The materials have been changed regionally. The differentiation on materials fix the dwellings ethnic qualities. Similar ones have been built with different technique and cultural diversities. xvni The material has been reed, tree brands mud, in northern valleys, wood and store in the mountain. The walls were built as two layers to get an insulation. The mud has been filling material for the structured shaped with other ones. The mud is applied or the indoor and outdoor surfaces as some kind of pilaster. This technique has been disappeared in later limes. The old houses, so called "long house" are independent units, which are organized axial by two or three rooms. The rooms are not open one to another. A large porch are attached to the whole front elevation functioning like sofa because of the rooms are opened to it. In Adigey and Kabardey regions, the porch can surround the whole building. The different types of roots are at hand according to the regional aspects. "V" shaped, pyramidal roofs are seen in the valleys, while the flat, earthy roofs are frequent on the mountains. In "V" shaped and pyramidal roofs, the beams are fixed on the lower walls and wooden construction is next to them. The reed and straw are plaited between them. The intersections of the roof and the walls are plastered by the mud, in order to get some kind of insulation. The floor finishing is the earth and there is not ceilings in common sense. The third chapter deals with the immigration to the Ottoman territories and especially to Düzce region with its geographical and seasonal layout. The living examples of the first settlements are given by means of photographs and drawings. Düzce region is at the western borders of Bolu. The optimum topographical height is 112m. with nice agricultural opportunities and dense population. Orhan, Kaplandere and Baba Mountains are at the north. Abant, Elmacık and Keremali Mountains are at the south of the region. The climate has Western Black Sea effects. The temperature conditions are characteristic for the Black Sea Region but freezes are frequent at Düzce. The dating is hand for the houses, but the people believe that they are 80 or 1 10 years old. Typology and structural qualities show that their ages are very close. The materials differ according to the construction time. Concrete and brick work are seen at the houses created in recent times. They are changed by the restorations and additions. Sometimes bathrooms and toilets are built or the new rooms are added following population growth. The porches are in some places original design but filled by parapets and walls in other ones. "Haçeş" in the gardens, have been used as the storage. The fire places and chimneys are out of use, in some dwellings. The roof tiles, the door and window frames or wings, the porch elements are renewed. The main load bearing material is wood. The wooden constructions have been shaped on the store foundations. The wooden elements which are shaping the structure have 15cm* 15cm. or 20cm.* 20cm. sections. The beams, under the walls are fixed on the foundations with others attached in every directions. The vertical elements up to the defined wooden construction is high enough to from the height of the dwelling. They are placed at the corners. The attaching beams up to theme frames also the roof structure is frame is straightened with wooden elements and plating is applied with the materials defined above. Plating differs between 12cm. and 17cm. according to the XIX sectional measurements formed by the wooden structure. The final step is the wall sections the filling of with mud, reed and the straw as well as plastering. The same procedure is applied also at the indoor and outdoor floors. The inter fillings of the floor finishing is realized with this composition, hardened by the water and pressed. The floor of the porches is 10cm.- 15cm. higher then the garden, just because of the defined application. The floors were earth filling, before 30 or 40 years ago, needed a certain care by water supply as a routine against the dust and a plain finishing daily. In later times, the same procedure is applied on the concrete surfaces. The wooden structure is filled by the brick work. The roof have generally wooden construction which also covers the porches. The wooden beam, which is forming the substructure for the roof comprised, the porch also. The juxtaposition with the substructure and the roof structure is realized by the integral elements or directly. The houses are parts of the large territories. They have been placed with the gardens, without a strict special contact with the roads or circulation patterns. The service spaces, as different parts of the settlements and so an. The toilets are without an optical contract with the porch as the common spaces. The haymow is not also, close to the dwellings with an entrance far enough from the general entrance to the garden. The space so called "kuruluk" is close to the house which has "haku" and "tuğu" under it. The storage and "haku" is constructed next to the each other with a common roof. The planning is very simple. The rooms are next to the each other. Some kind of rectangular design have been shaping the spaces. They are independent, and do not open one to the each other as the access is formed by the porch or garden. The spatial organization is common with three rooms, the fire place is frequently at the middle one. The closets are seen at each room. Some are preserved for the bathrooms, the others are for the kitchen and living services. The floors heights at the interconnecting openings are low. Heightening the floors creates higher thresholds. The rooms at the front rear elevations have got large windows. The window openings at the rear elevations at the middle. Framing at the windows and the doors are large enough. The elevations are simple. The design is elaborated by the vertical elements of the porches or the window patterns. The privacy is integrated by means of space awareness, especially as the dividing patterns of the porch. The staircase lacking on the indoors. One or two steps are provided for an access to the porch, in some dwellings. If the access is needed from the garden, the steps are stone work and as large as the door frames. The fourth chapter is the comparison between the quarters of the immigrants and the traditional ones at the motherland, with some focus on the differences. XX Available examples are not developed ones, as we are talking about traditional Caucasian houses. They are formed traditionally, from the independent units axially attached. The houses that we met at Düzce region is very similar to the traditional dwellings from Adigey region of the motherland. The construction is wooden work, frequently following tradition like the filling patterns, same as the ones from the Northern Caucasia. The materials that are defined above have been longtime used in Northern Caucasia too. Construction and structural patterns have also very significant similarities as the foundation and floors which have not been changed on the new habitations erected to the new settlements. The differences are first seen at the materials, used to fill the structure. The brick work and mud brick construction are first used at the beginning of the 19.th century in Caucasian territories. The straw and mud filling are used for reed plating if the construction is wooden work, then the mud has been used not as a filling material but as plastering element for the indoor and outdoor surfaces. The houses built on Turkish territories differs according to their site in the gardens. They have got a certain contact with street patterns. The other differentiation consist of by the first places, their location in the rooms, the window measurements, the roof structure and roof finishing.
Notrhern caucasian houses in düzce
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Keywords: Bolu-Düzce; Kuzey Kafkasya; Çerkeş evleri; Bolu-Düzce; North Caucasia; Çerkeş houses